Reflection on my 37 years practice as a neuropathologist: Home alone. - Popović, Mara (Free Neuropathology, 2020)
I was born 70 years ago in the small town of Sinj, Dalmatia, Croatia, Yugoslavia. When I was 5 months old, my father was sent to prison for two years on Goli otok (Bare Island), an ill-famed prison for politically inappropriate people at that time. At 24 years old, he could not understand that Stalin, who was an idol for young Communists, had become an enemy overnight after the Informbiro Resolution, by which the Yugoslav Communist party was expelled from the international Communist party led by Stalin. It was a price for living free on the outer side of the Iron Curtain, between East and West, where Yugoslavia remained until the end of 1990, when the Balkan wars started. My father has stuck with Communist ideas until today, almost 95 years old. Under his influence, I entered the Communist party in high school, but very quickly realized that politics is not something I would like to practice.